Handbook of digital forensics and investigation - Casey, Eoghan; Altheide, Cory. (Burlington, Mass. : Academic Press, 2010)
The Handbook of Digital Forensics and Investigation builds on the success of the Handbook of Computer Crime Investigation, bringing together renowned experts in all areas of digital forensics and investigation to provide the consummate resource for practitioners in the field. This unique collection details how to conduct digital investigations in both criminal and civil contexts, and how to locate and utilize digital evidence on computers, networks, and embedded systems. Specifically, the Investigative Methodology section of the Handbook provides expert guidance in the three main areas of pra.
pt. 1. Investigative methodology -- pt. 2. Technology.
Includes bibliographical references and index.
Print version record.
Keywords: Computer crimes -- Investigation; Evidence, Criminal; Criminalité informatique -- Enquêtes.; Preuve (Droit pénal); LAW -- Forensic Science; Computer crimes -- Investigation; Evidence, Criminal